Influence of visual training programmes on the performance of the novice tennis player approaching the net - del Campo, V. L.; Reina Vaillo, R.; Sanz Rivas, D.; Moreno Hernandez, F. J. (Medicine and Science in Tennis, 2004)
This study applies the concepts of motor learning and control to the training process in tennis. It analyses the influence of several visual training programmes on reaction response time and precision of response in 40 novice tennis players, both in a laboratory setting and on court. An approach shot situation is simulated, whereby the player has to react quickly and precisely in an attempt to win the point with a volley. These programmes, based on anticipation, seek to improve reaction response time and to increase the number of correct responses to the specific task.